90.2k views
1 vote
Solve for x:
-3x + 2 = 2x + 37

2 Answers

6 votes

To solve for x, you need to isolate/get the variable "x" by itself in the equation:

-3x + 2 = 2x + 37 Add 3x on both sides to get "x" on one side of the equation

-3x + 3x + 2 = 2x + 3x + 37

2 = 5x + 37 Subtract 37 on both sides (you could have subtracted 2x instead of adding 3x, and subtract 2 instead of 37)

2 - 37 = 5x + 37 - 37

-35 = 5x Divide 5 on both sides to get "x" by itself


(-35)/(5) =(5x)/(5)

-7 = x

PROOF

-3x + 2 = 2x + 37 Substitute/plug in -7 into "x" since x = -7

-3(-7) + 2 = 2(-7) + 37 (two negative signs cancel each other out and become positive)

21 + 2 = -14 + 37

23 = 23

User Amaranth
by
6.1k points
3 votes

Answer:39

Explanation:

User Russell Dias
by
5.8k points